ANALISIS KELAYAKAN USAHATANI PAPRIKA DENGAN PENGGUNAAN SISTEM IRIGASI PRESISI - Hotnauli Odelia; Lies Sulistyowati (Universitas Galuh Ciamis, 2020)
Paprici Segar Barokah made additional investments in encomotion technology in paprika farming. Although encomotion innovation is expected to increase productivity, investment in business development requires a substantial cost. The purpose of this study was to analyze the feasibility of paprika farming with a qualitative research method located in Paprici Segar Barokah. Data obtained from interviews, secondary data and other literature. Analysis of the data used is the financial feasibility analysis (NPV, IRR, Net B / C and PP) and non-financial with two scenarios, namely the farming of precision irrigation and manual irrigation. In addition, a sensitivity analysis using switching value is also carried out. The results showed that from the financial aspects of precision irrigation paprika farming had an NPV of Rp. 58,378,184, IRR 27.64 percent, Net B / C 1.807 and PP for 3 years and 8 months, showing better indicators than the feasibility analysis of manual irrigation farming (NPV Rp. 1,479,172, IRR 7.18%, Net B / C 1.022 and Payback period is 4 years 11 months). Based on the results of switching value analysis, farming of manual irrigation systems has a higher sensitivity than precision irrigation.